2016
DOI: 10.1038/aps.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine use in current clinical practice

Abstract: After nearly half a century on the market, ketamine still occupies a unique corner in the medical armamentarium of anesthesiologists or clinicians treating pain. Over the last two decades, much research has been conducted highlighting the drug's mechanisms of action, specifically those of its enantiomers. Nowadays, ketamine is also being utilized for pediatric pain control in emergency department, with its anti-hyperalgesic and anti-inflammatory effects being revealed in acute and chronic pain management. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
123
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 104 publications
1
123
0
7
Order By: Relevance
“…Since its first clinical use in 1970, ketamine has continued to remain a critical component of the medical arsenal of anaesthesiologists and clinicians treating both acute and chronic pain, in particular finding a growing use in the management of adult and paediatric burns. [7] Over the past two decades, several studies have investigated the additional antidepressant and anti-inflammatory effects of ketamine. [7][8][9] The appeal of ketamine in the clinical setting is its versatility as a result of its unique ability to induce three clinical outcomes, i.e.…”
Section: Defining the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its first clinical use in 1970, ketamine has continued to remain a critical component of the medical arsenal of anaesthesiologists and clinicians treating both acute and chronic pain, in particular finding a growing use in the management of adult and paediatric burns. [7] Over the past two decades, several studies have investigated the additional antidepressant and anti-inflammatory effects of ketamine. [7][8][9] The appeal of ketamine in the clinical setting is its versatility as a result of its unique ability to induce three clinical outcomes, i.e.…”
Section: Defining the Problemmentioning
confidence: 99%
“…[7] Over the past two decades, several studies have investigated the additional antidepressant and anti-inflammatory effects of ketamine. [7][8][9] The appeal of ketamine in the clinical setting is its versatility as a result of its unique ability to induce three clinical outcomes, i.e. narcosis, analgesia and amnesia.…”
Section: Defining the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine [2‐( o ‐chlorphenyl)‐2‐methylamino cyclohexanone] is a phencyclidine derivative with unique analgesic, amnestic, and dissociative properties . It acts primarily as a competitive antagonist at the N ‐methyl‐ d ‐aspartate (NMDA) receptor within the limbic system to modulate autonomic responses to stimuli . As a treatment option for pain, ketamine has numerous advantages over opioids including a stable hemodynamic profile and lack of respiratory depression .…”
mentioning
confidence: 99%
“…It acts primarily as a competitive antagonist at the N ‐methyl‐ d ‐aspartate (NMDA) receptor within the limbic system to modulate autonomic responses to stimuli . As a treatment option for pain, ketamine has numerous advantages over opioids including a stable hemodynamic profile and lack of respiratory depression . Recent studies have demonstrated ketamine's effectiveness for pain control in patients who present to the ED with acute pain syndromes when infused in a subdissociative dose by itself or in conjunction with NSAIDs .…”
mentioning
confidence: 99%